Disruption of Golgi morphology and altered protein glycosylation in PLA2G6-associated neurodegeneration. Issue 3 (14th December 2015) - Davids, Mariska; Kane, Megan S; He, Miao; Wolfe, Lynne A; Li, Xueli; Raihan, Mohd A; Chao, Katherine R; Bone, William P; Boerkoel, Cornelius F; Gahl, William A; Toro, Camilo
Abstract : Background: Mutations in PLA2G6, which encodes the calcium-independent phospholipase A2 group VI, cause neurodegeneration and diffuse cortical Lewy body formation by a yet undefined mechanism. We assessed whether altered protein glycosylation due to abnormal Golgi morphology might be a factor in the pathology of this disease. Methods: Three patients presented with PLA2G6 -associated neurodegeneration (PLAN); two had infantile neuroaxonal dystrophy (INAD) and one had adult-onset dystonia-parkinsonism. We analysed protein N-linked and O-linked glycosylation in cerebrospinal fluid, plasma, urine, and cultured skin fibroblasts using high performance liquid chromatography (HPLC) and matrix-assisted laser desorption ionisation - time of flight/mass spectrometry (MALDI-TOF/MS). We also assessed sialylation and Golgi morphology in cultured fibroblasts by immunofluorescence and performed rescue experiments using a lentiviral vector. Results: The patients with INAD had PLA2G6 mutations NM_003560.2: c.[950G>T];[426–1077dup] and c.[1799G>A];[2221C>T] and the patient with dystonia-parkinsonism had PLA2G6 mutations NM_003560.2: c.[609G>A];[2222G>A]. All three patients had altered Golgi morphology and abnormalities of protein O-linked glycosylation and sialylation in cultured fibroblasts that were rescued by lentiviral overexpression of wild type PLA2G6. Conclusions: Our findings add altered Golgi morphology, O-linked glycosylation and sialylation defects to the phenotypical spectrum of PLAN; these pathways are essential for correct processing and distribution of proteins. Lewy body and Tau pathology, two neuropathological features of PLAN, could emerge from these defects. Therefore, Golgi morphology, O-linked glycosylation and sialylation may play a role in the pathogenesis of PLAN and perhaps other neurodegenerative disorders.